Monetary policy transmission in South Africa: the prime rate-demand for credit phase - Lehobo, Limakatso (Rhodes University, Faculty of Commerce, Department of Economics, 2006)
A voluminous literature attempts to explain the various channels of the monetary policy transmission mechanism through which central banks ultimately achieve price stability. However, most research focuses on interest rate pass-through and the demand for money phase, while there is limited research on the demand for credit. This study endeavours to contribute to the understanding of this neglected phase of monetary policy transmission by exploring the response of the real demand for bank credit by the private sector to changes in the real prime rate from 1990:1 to 2004:4 in South Africa. Firstly, the behaviour of the real prime rate in relation to the repo rate is explored using graphical analysis. The study observes that an increase in the repo rate causes an increase in the real prime rate, such that there is always a margin of three or four percentage points between the two rates. Secondly, using secondary data, the Johansen methodology is used to determine the relationship between the demand for bank credit and its determinants (GDP, inflation, real prime rate and real yield on government bonds). Two co-integrating relationships are found. The Gaussian errors from one co-integrating vector are used to model the Vector Error Correction Model, which provides the short-run dynamics and the long-run results, through the use of Eviews 5 software. The results of the study show that while all other variables are negatively related to the demand for bank credit in the long-run, GDP has a positive influence. In the short-run, yield on government bonds and inflation coefficients depict a positive association, while the coefficients of real prime rate and GDP are negative. The error correction coefficient is -0.32, which implies that a 32% adjustment to equilibrium happens in the demand for bank credit in a quarter and that the complete adjustment takes about three quarters to complete. Thirdly, the generalised impulse responses results indicate that the impact on the real prime rate affects the demand for bank credit from the first quarter. The study concludes that the real prime rate has a negative impact on the demand for credit both in the short-run and long-run.
Keywords: South African Reserve Bank; Monetary policy -- South Africa; Banks and banking -- South Africa; Bank loans -- South Africa; Financial institutions -- South Africa; Finance -- South Africa